2012
DOI: 10.1073/pnas.1207917109
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-494 is regulated by ERK1/2 and modulates TRAIL-induced apoptosis in non–small-cell lung cancer through BIM down-regulation

Abstract: MicroRNAs (miRNAs) have an important role in the development of chemosensitivity or chemoresistance in different types of cancer. Activation of the ERK1/2 pathway is a major determinant of diverse cellular processes and cancer development and is responsible for the transcription of several important miRNAs. Here we show a link between the ERK1/2 pathway and BIM expression through miR-494. We blocked ERK1/2 nuclear activity through the overexpression of an ERK1/2 natural interactor, the protein PED/PEA15, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
137
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 31 publications
(33 reference statements)
4
137
0
2
Order By: Relevance
“…24 Searching in different databases, we did not identify previous reports relating the other 13 miRNAs reported in Figure 3 and Table 1 with resistance of NSCLC cells to doxorubicin or other chemotherapeutic agents. This finding adds new miRNAs and opens the avenue for new targets/predictors to improve the response of lung cancer cells to chemotherapy.…”
Section: Discussionmentioning
confidence: 83%
“…24 Searching in different databases, we did not identify previous reports relating the other 13 miRNAs reported in Figure 3 and Table 1 with resistance of NSCLC cells to doxorubicin or other chemotherapeutic agents. This finding adds new miRNAs and opens the avenue for new targets/predictors to improve the response of lung cancer cells to chemotherapy.…”
Section: Discussionmentioning
confidence: 83%
“…Ohdaira et al found that miR-494 suppressed cell proliferation and induced senescence in A549 lung cancer cells (Ohdaira et al 2012). Furthermore, Romano et al (2012) found that miR-494 was regulated by ERK1/2 and modulated by tumor necrosis factorrelated apoptosis-inducing ligand-induced apoptosis in non-small-cell lung cancer through BIM downregulation. The findings by Kim et al (2011) indicated that miR-494 was a negative regulator of KIT in gastrointestinal stromal tumors (GISTs), and overexpressing miR-494 in GISTs might be a promising approach to GIST treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that mir-494 was downregulated and functioned as a tumor suppressor in human cholangiocarcinoma (21), gastric cancer (23) and lung cancer (28). However, other studies demonstrated that upregulation of mir-494 was associated with several types of human malignant solid tumors, including hepatocellular carcinoma (29), non-small cell lung cancer (30), and carcinoma induced by anti-BPDe (27). in these types of cancer, mir-494 seemed to be an oncogene, and promoted tumor cell proliferation, cell cycle, cell migration and invasion via regulation of the target genes Pten, BiM and Mcc.…”
Section: Discussionmentioning
confidence: 99%